Skin Aging and Herbal Anti-Aging Serums: A Comprehensive Review - Dileep, Shintre Aniruddha; Dayanand, Naikawadi Nishigandha; Redasani, Dr. V.K. (Asian Journal of Pharmaceutical Research and Development, 2024)
This review explores the intricate anatomy of the skin, giving a brief synopsis of its structure and role. It describes the various aspects of skin aging and the roles that both intrinsic and extrinsic factors play in this process of aging. Focusing on the topic of herbal medicines, the article investigates the scientifically proven anti-aging properties of a variety of herbs. It also provides information about the composition and varieties of serums, emphasizing important components such hyaluronic acid, vitamin C, vitamin B3, and herbal extracts that are effective in preventing facial ageing. The aim of this review is to provide readers with a comprehensive understanding of skin aging and the wide range of anti-aging techniques accessible, especially in the context of herbal based face serum